A new language for creativity in fashion design - Broega, A. C. (2012)
The development of innovative products in all business areas passes through different stages, starting with the research followed by creation until the project's conclusion. The creative process in shoes and clothing design involves the ability to group and rearrange existing elements, ideas and techniques for achieving solutions to meet the presented challenges. The creation process demystifies and breaks rules and put concepts together, so that, in the end, it can introduce a new language to fashion products. This study investigates the difficulties that creative professionals face when developing creative work for companies and the way that external factors can positively or negatively affect the development of new ideas. It also investigates the factors that can motivate the continuous work of fashion designers so their creative potential is not blocked. Throughout the study, theories of various authors were analyzed, discussed techniques on how to spark creativity, showing methods of how to facilitate the performance of the creative professional within an organization, so they can use the information in the best way to renew their creative potential. The results show that there are effective techniques to stimulate the creative, whether it is arising from a simple collection of past experiences, or from more elaborate techniques such as brainstorming, analogies, fractionation, suspension of value judgments, and challenge assumptions, among others suggested by De Bono.